2015
DOI: 10.1016/j.ajodo.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Hounsfield unit change in root and alveolar bone during canine retraction

Abstract: Objectives The objective of this study was to determine the Hounsfield unit (HU) changes in the alveolar bone and root surface during controlled canine retractions. Methods Eighteen maxillary canine retraction patients were selected for this split mouth design clinical trial. The canines in each patient were randomly assigned to receive either translation or controlled tipping treatment strategy. Pre- and post-treatment cone beam computed tomography scans of each patient were used to determine tooth movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
2
7
1
Order By: Relevance
“…It had been reported previously that no significant difference of BMD change patterns had been detected in the surrounding alveolar bone under the two treatment strategies . This is in agreement with our stress analysis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It had been reported previously that no significant difference of BMD change patterns had been detected in the surrounding alveolar bone under the two treatment strategies . This is in agreement with our stress analysis.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it is helpful to see whether the initial ME change in terms of each of the stress invariants is related to the BMD reduction, which may indicate whether certain ME change triggers the bone activities. In this discussion, the BMD were expressed in terms of HU as was reported previously .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 We are fully aware of the limitation of using Hounsfield units (HU) to predict bone mineral density (BMD) from cone-beam computed tomography (CBCT) images; this was the reason that we designed this longitudinal study and only reported the relative HUs or HU changes. We chose HUs because they are commonly associated with BMD.…”
mentioning
confidence: 99%